To Return or Not to Return: A Dilemma of Two Overseas Vietnamese Students in the Netherlands Amidst the Coronavirus Outbreak - Cao, Thai Quoc; Chieu, Quynh Kim (Journal of International Students, 2021)
Amidst the worldwide outbreak of the coronavirus, many overseas Vietnamese students have decided to return to Vietnam to seek protection from illness. However, the decision to return in such a risky context requires intensive thinking about the outcomes of each possible choice. The aim of this reflection paper is to explore the personal considerations and dilemmas during the decision-making process of two Vietnamese students in the Netherlands using the expected utility framework. The experience of applying a systematic approach to assess risky situations not only informs decisions more comprehensively but also provides an opportunity to look deeply at one’s values and interests.